Effect of the immobilized microcystin-LR-degrading enzyme MlrA on nodularin degradation and its immunotoxicity study. (March 2020) - Wu, Xiang; Wu, Hao; Gu, Xiaoxiao; Zhang, Rongfei; Sheng, Qiang; Ye, Jinyun
Abstract: In freshwater ecosystems with frequent cyanobacterial blooms, the cyanobacteria toxin pollution is becoming increasingly serious. Nodularin (NOD), which has strong biological toxicity, has emerged as a new pollutant and affects the normal growth, development and reproduction of aquatic organisms. However, little information is available regarding this toxin. In this study, a graphene oxide material modified by L-cysteine was synthesized and used to immobilize microcystin-LR (MC-LR)-degrading enzyme (MlrA) to form an immobilized enzyme nanocomposite, CysGO-MlrA. Free-MlrA was used as a control. The efficiency of NOD removal by CysGO-MlrA was investigated. Additionally, the effects of CysGO-MlrA and the NOD degradation product on zebrafish lymphocytes were detected to determine the biological toxicity of these two substances. The results showed the following: (1) There was no significant difference in the degradation efficiency of NOD between CysGO-MlrA and free-MlrA; the degradation rate of both was greater than 80% at 1 h (2) The degradation efficiency of the enzyme could retain greater than 81% of the initial degradation efficiency after the CysGO-MlrA had been reused 7 times. (3) CysGO-MlrA retained greater than 50% of its activity on the 8th day when preserved at 0 °C, while free-MlrA lost 50% of its activity on the 4th day. (4) CysGO-MlrA and the degradation product of NOD showed no obvious cytotoxicity to zebrafish lymphocytes. Therefore, CysGO-MlrA might be used as an efficient and ecologically safe degradation material for NOD. Graphical abstract: Image 108456 Highlights: Both CysGO-MlrA and free-MlrA can effectively degrade the Nodularin (NOD). CysGO-MlrA can reuse more times and keep its activity longer than free-MlrA. CysGO-MlrA and the degradation product of NOD showed no immunotoxicity of zebrafish. CysGO-MlrA is an efficient and ecologically safe degradation material for NOD. Abstract : CysGO-MlrA can be used as an efficient and ecologically safe degradation material for nodularin.